Upgrading of isolated bridges with space-bar energy-dissipation devices: Shaking table test. Issue 13 (October 2021) - Ristic, Jelena; Brujic, Zoran; Ristic, Danilo; Folic, Radomir; Boskovic, Milos
The results of the experimental research program realized on a bridge model constructed by using the seismically isolated system upgraded with space-bar devices (USI-SB) are presented in the paper. The installed adaptable system for seismic protection of bridges utilizes double spherical rolling seismic bearings (DSRSB) as seismic isolators, while the qualitative improvement of seismic performances is achieved through the use of novel adjustable multi-directional space-bar energy dissipation (SB-ED) devices. The experimental program consisted of quasi-static testing of isolation and energy dissipation devices under the cyclic loading and extensive shaking-table testing of a large-scale bridge model with installed USI-SB system. For both types of devices, a very stable all-directional response during cycling tests, as well as the favorable hysteretic behavior of the energy dissipation devices along the entire range of applied large displacements were registered. In the dynamic testing, the system showed high seismic response modification performances needed for the efficient protection, exhibiting its large potential in the qualitative improvement of seismic performances of isolated bridges.